Probiotics Do Not Alter the Long-Term Stability of the Supragingival Microbiota in Healthy Subjects: A Randomized Controlled Trial - Lundtorp-Olsen, Christine; Enevold, Christian; Twetman, Svante; Belstrøm, Daniel (Pathogens (Basel), 2021)
Background: The purpose of the present study was to longitudinally characterize the supragingival microbiota throughout a three months period in orally healthy individuals. We tested the hypothesis that the supragingival microbiota shows a high degree of compositional stability, which is resilient against the external perturbation of regular use of probiotics, as long as oral health is maintained. Methods: The present study was a double-blinded, randomized, placebo-controlled clinical trial. The study population comprised a total of 110 oral and systemic healthy individuals, distributed in a probiotic (n = 55) and placebo (n = 55) group, where the test group consumed tablets with the probiotic strains Lacticaseibacillusrhamnosus (formerly Lactobacillus) PB01 DSM14870 and Latilactobacillus curvatus (formerly Lactobacillus) EB10 DSM32307 for a period of 12 weeks. Supragingival plaque samples and clinical registrations were performed at baseline, and after 4, 8, and 12 weeks, respectively. The supragingival microbiota was characterized by means of 16S rDNA sequencing. Sequences were referenced against the HOMD database. Results: No significant changes of the core microbiota, as expressed by relative abundance of predominant genera and species were evident during the three months observation period in the probiotic or the placebo group. Conclusions: Data from the present study clearly demonstrate long term compositional stability of the supragingival microbiota as long as oral health is maintained. In addition, the tested probiotics had no augmenting effect on the supragingival microbiota in oral health.